2012
DOI: 10.1245/s10434-012-2326-2
|View full text |Cite
|
Sign up to set email alerts
|

Hospital and Medical Care Days in Pancreatic Cancer

Abstract: Background Little is known about resource utilization (number of days in the hospital or medical care) between diagnosis and death in patients with pancreatic cancer. Methods Using Surveillance, Epidemiology, and End Results (SEER)-Medicare linked data, we identified 25,476 patients with pancreatic cancer (1992-2005). Hospital and medical care days per person-month from the time of diagnosis were described, stratified by stage, treatment, and survival duration. Results Hospital/medical care days vary by le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Another study in patients with pancreatic cancer looked at the number of hospital and medical care days between diagnosis and death and found that these individuals spent an average of 6.4 days in the hospital and 9.0 days receiving medical care in the first month after diagnosis, decreasing to 1.7 and 3.7 days per month in the year after diagnosis. Although this study did look at where time was spent beyond 30 days, only 9.1% of their study population underwent surgery, compared with 100% of our study cohort …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Another study in patients with pancreatic cancer looked at the number of hospital and medical care days between diagnosis and death and found that these individuals spent an average of 6.4 days in the hospital and 9.0 days receiving medical care in the first month after diagnosis, decreasing to 1.7 and 3.7 days per month in the year after diagnosis. Although this study did look at where time was spent beyond 30 days, only 9.1% of their study population underwent surgery, compared with 100% of our study cohort …”
Section: Discussionmentioning
confidence: 82%
“…Although this study did look at where time was spent beyond 30 days, only 9.1% of their study population underwent surgery, compared with 100% of our study cohort. 17 Our study is novel in its aim to document the amount of time spent away from home (ie, in a hospital and/or in a nursing home) for the entire year following high-risk cancer surgery. The proportion of days spent at home is a new and important patient-centered quality metric used in the nonsurgical literature, reflecting both intuition and academic research that suggests that individuals prefer to be at home, particularly in their final days of life.…”
Section: Discussionmentioning
confidence: 99%